P5_8 A Mechanised Mitigation of a Mayonnaise Mess-Up - Rayson, Ben; Sharman, Mark; Molloy, David; Knott, George (Physics Special Topics, 2022)
In this paper, an analysis is carried out of an aviation propeller strapped to an office chair as a life-saving device. If one were to find themselves in trouble, this device would be able to hold a human atop the mayonnaise surface, averting disaster. The rotational speed necessary for the propeller was calculated in this paper via consideration of the coefficient of thrust. The rate required was found to be 6.5804 rad/s.